Етапи реалізації програми фізичної реабілітації слабозорих та незрячих дітей дошкільного віку - Григус, Ігор Михайлович; Нагорна, Ольга Борисівна; Примачок, Людмила Леонтіївна; Небова, Наталія Анатоліївна; Ніколенко, Олександр Іванович; Hryhus, Ihor; Nahorna, Olha; Prymachok, Lyudmyla; Nebova, Nataliya; Nikolenko, Oleksandr (Східноєвропейський національний університет імені Лесі Українки, 2018)
У статті висвітлено проблеми розвитку рухових функцій дітей зі слабозорістю та тотальною сліпотою. Отже, формування рухових функцій, орієнтаційних уявлень, ігрової діяльності незрячої дитини вимагає цілеспрямованого реабілітаційного втручання. Мета дослідження – визначити організаційно-методичні особливості реалізації програми фізичної реабілітації сліпих дітей дошкільного віку. Завдання дослідження – проаналізувати спеціальну науково-методичну літературу з проблеми дослідження; визначити спрямованість, завдання, засоби поетапного реабілітаційного супроводу слабозорих і з тотальною сліпотою дітей. Розглянуто етапи фізичної реабілітації дітей із порушеними функціями зорового аналізатора в процесі навчання цілеспрямованих рухових дій. Акцентовано увагу на необхідності покращення якості ходьби незрячих дітей дошкільного віку та формуванні участі й активності, а також незалежності в побуті. Відзначено, що чим більше аналізаторних систем задіюється в процесі сприйняття та оволодіння руховими діями дітьми з вадами зору, тим цілісніше й повніше уявлення про них, ефективніше відбувається процес корекційного навчання та вдосконалення моторних функцій. Розглянуто етапи формування просторового орієнтування, ігрової діяльності сліпих дітей. Запропоновано способи покращення локомоцій незрячих дошкільнят засобами фізичної реабілітації. Реабілітаційний супровід слабозорих і сліпих дітей складається з етапів, які мають свою мету, завдання та зміст занять з урахуванням вікових, когнітивних факторів й анамнезу; запропонована поетапна реалізація довгострокових і короткострокових завдань програми фізичної реабілітації дає змогу створити в дітей адекватне уявлення про рухові функції, якість їх виконання й застосування. The article deals with the problems of development of motor functions of children with low vision and total blindness. Thus, the formation of motor functions, orientation representations, and the gaming activity of the blind child requires purposeful rehabilitation intervention. The purpose of the study: to determine the organizational and methodical features of the program of physical rehabilitation of blind children of preschool age. Objectives of the study: to analyze special scientific and methodological literature on the research problem; to determine orientation, a task, means of phased rehabilitation of the visually impaired children with total blindness. The following research methods, such as the analysis and synthesis of scientific literary sources, clinical practical experience of working with this nosological group of children, pedagogical observation, generalization and systematization of the results of the research were used to solve the problems. The stages of physical rehabilitation of children with impaired functions of the visual analyzer in the process of training of purposeful motor actions are considered. The emphasis is on the need to improve the quality of walking of blind children of preschool age and the formation of participation and activity, as well as independence in everyday life. It is noted that the more analyzer systems are used in the process of perceiving and mastering motor activity by children with visual impairments, the more holistic and complete representation of them, the process of correction training and improvement of motor functions is effective. The stages of formation of spatial orientation, playing activity of blind children are considered. The ways of improvement of locomotions of blind preschoolers by means of physical rehabilitation are offered. Summarizing the results of the study, we can draw the following conclusions: rehabilitation of visually impaired and blind children consists of stages, which have their goals, tasks and content of classes, taking into account age, cognitive factors and anamnesis; the proposed phased implementation of long-term and short-term tasks of the program of physical rehabilitation allows children to create an adequate understanding of motor functions, the quality of their implementation and application; for the positive result of rehabilitation and correctional influence on the quality of performance of a specific motor function, it is necessary to form the need for its application in the everyday life of the child; implementation of the program of physical rehabilitation in the program of preschool preparation of blind children contributes to the development of qualitative and quantitative characteristics of the performed locomotions and the process of formation of motor skills and everyday skills, the development of their physical condition in general.
Stages of Implementation of the Program of Physical Rehabilitation of Visually Impaired and Blind Children of Preschool Age
Keywords: дошкільники з порушеннями зору; сліпі діти; просторове орієнтування; ігрова діяльність; локомоції; фізична реабілітація; рухова дія; етапи корекції; моторні функції; preschool children with visual impairment; blind children; spatial orientation; play activity; locomotion; physical rehabilitation; motor performance; correction stages; motor function